Description and selection within a peach backcross population and parental segregation for the aptitude for fruits postharvest conservation trait - Chirino, Julian Santiago; Gabilondo, Julieta; Budde, Claudio Olaf; Valentini, Gabriel Hugo; Sanchez, Gerardo (Centro Regional Córdoba, INTA, 2022)
Poster